Pengaruh Pemberian Insentif dan Motivasi Kerja Terhadap Kinerja Karyawan Bagian Penagihan Pada Perusahaan Daerah Air Minum (PDAM) Tirta Manakarra Kabupaten Mamuju - Halim, Agus; Asriana, Asriana (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
The method used is the Quantitative Method by distributing questionnaires/questionnaires. The sample used in this study the sample used was 30 employees. The sampling technique used non-probability sampling with total sampling technique, in this study all the population was sampled with a total of 30 respondents. Data processing techniques by testing research instruments using reliability tests and multiple linear regression analysis. While the hypothesis test using Simultaneous Test (f test) and the correlation coefficient (R) and the coefficient of determination (R2).The results of this study indicate that 1) The results of the multiple linear regression partially indicate the provision of incentives with a significant value of 0.006 <0.05 and a tcount value of 5.918 > a t-value of 1.68830, work motivation with a significant value of 0.012 <0.05 and a t-value of 3.598 > ttable value 1.68830, so it can be concluded that the two independent variables have a significant effect on the dependent variable partially or one by one, thus the hypothesis is accepted. 2) The results of multiple linear regression tests simultaneously show that the provision of incentives is the most dominant variable that has a significant influence on the performance of the billing department employee at the Tirta Manakarra Regional Drinking Water Company (PDAM) Mamuju Regency.